How Nucleic acids DNA and RNA are Misrepresented by Tortured Phrases - Teixeira da Silva, Jaime A. (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: Deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) are established terms in genetics and molecular biology literature, so linguistic deviations from these terms would be equivalent to their scientific misrepresentation. This paper aimed to identify literature containing the term “nucleic corrosive,” which is a ‘tortured phrase’ (TP), and the misrepresentation of jargon related to nucleic acid. METHODOLOGY: The Tortured Phrase Detector of the Problematic Paper Screener (PPS) was consulted on 11 May 2025 to identify documents of any type with this TP. RESULTS: At PPS, a total of 71 indexed and accessible documents (44 articles, 18 book chapters, seven proceedings papers and two preprints) with a DOI, 35 (49%) of which were open access, were identified. Most documents (54; 76%), which were published between 2017 and 2024, had an affiliation in India. Four of the documents have been retracted. The publishers with the highest incidence of documents containing the “nucleic corrosive” TP were Elsevier and Springer Nature: 21 (30%) and 13 (18%), respectively. CONCLUSION: The existence of TPs in these documents, except for the preprints, points towards failure in quality control at the levels of peer review, editorial handling and copy editing.